Cos catalyst for the replacement of fossil fuels to biofuels / Z. A. Alexzman ... [et al.] - Alexzman, Z. A.; Annuar, N. H. R.; Daud, A. R. M.; Ibrahim, M. L.; Salamun, N. (2022)
One of the major factors of climate change is the increase in greenhouse gas emissions caused by the increased usage of fossil fuels. An alternate strategy for dealing with this issue is the conversion of biomass into useful compounds by a hydrogenolysis reaction, particularly through the catalytic hydrogenolysis of sorbitol. Its industrial application has, regrettably, been constrained by the catalyst's deactivation. Therefore, there is a lot of interest in developing new, attractive catalysts that could improve the performance of the hydrogenolysis reaction. Catalytic performance is greatly influenced by the effects of the metal (monometallic and bimetallic), the supporting material, and the acid/base characteristics. Chromium Oxide Silica (CoS) is a famous catalyst for polymerization of ethylene at relatively low pressures, hydrogenation-dehydrogenation, oxidation, isomerization and complete combustion. In this study, CoS catalyst with 15wt% Cr2O3 loadings was synthesized using impregnation method, to gain a better understanding on the nature of chromium oxide species on the silica. The samples (SiO2 and 15wt%CoS) were analyzed using SEM, XRD, FTIR, TGA and DSC to confirm the formation of CoS. FTIR spectra and XRD pattern showed successful incorporation of Cr2O3 on SiO2 support. SEM images indicated that the samples prepared have a uniform size and start to agglomerate when chromium oxide was introduced. Meanwhile, TGA analysis showed the stability of both samples even after they were calcined at high temperature. In summary, these catalyst properties can be used as the starting point for catalytic reactions and large-scale applications.